IMPROVING STUDENTSâ LISTENING-RESPONSE SKILL - Rifqi, Muhammad (LITE, 2007)
Responding to questions is an important skill to develop.Sometimes students cannot give suitable responses to somespecific questions. In order to be able to give suitable response to a question students have to understand what a given questionexpects. Failing to anticipate what the question asks will lead thestudents to give unsuitable response. Giving feedback to thestudents in anticipating what a question asks is believed to be able to improve their abilities to respond to the questions appropriately. I conducted classroom research on the teacherâs feedback to improve the studentsâ question-response skill in my listening class in EFL setting. Sixty-nine participants were the fourthsemester students taking Listening IV in 2005. They were asked to listen to and answer the recorded oral questions taken from a standardized model test. The test results were evaluated and the researcher gave feedback to the students by giving the key and discussing the case specific to each question item. After giving teacherâs feedback, the participants were asked to listen and respond to a number of questions and the result, again, wereevaluated. This cycles were iterated for 3 times. The teacherâsfeedback comprises sound recognition, guessing the wordâs orphraseâs meaning, and grammar. The research findings showed significant improvement on the studentsâ question-response skill indicated by the increased mean score especially after implementing the third cycle.Keywords: feedback, action research, cycles, sound recognition,meaning, grammar